Single-molecule visualization of conformational changes and substrate transport in the vitamin B(12) ABC importer BtuCD-F - Goudsmits, Joris M. H. (Nat Commun, 2017)
ATP-binding cassette (ABC) transporters form the largest class of active membrane transport proteins. Binding and hydrolysis of ATP by their highly conserved nucleotide-binding domains drive conformational changes of the complex that mediate transport of substrate across the membrane. The vitamin B(12) importer BtuCD-F in Escherichia coli is an extensively studied model system. The periplasmic soluble binding protein BtuF binds the ligand; the transmembrane and ATPase domains BtuCD mediate translocation. Here we report the direct observation at the single-molecule level of ATP, vitamin B(12) and BtuF-induced events in the transporter complex embedded in liposomes. Single-molecule fluorescence imaging techniques reveal that membrane-embedded BtuCD forms a stable complex with BtuF, regardless of the presence of ATP and vitamin B(12). We observe that a vitamin B(12) molecule remains bound to the complex for tens of seconds, during which several ATP hydrolysis cycles can take place, before it is being transported across the membrane.